2023
DOI: 10.3390/healthcare11091341
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Left–Right Side Differences of Sagittal Condylar Inclination (SCI) in Different Skeletal Classes

Andi Ciprian Dragus,
Augustin Mihai,
Gabriela Tanase
et al.

Abstract: (1) Background: The temporomandibular joint (TMJ) is the most complex and one of the most important joints in the human body due to its essential roles in mastication, swallowing, breathing and speech. Several instruments have been used to track mandibular movements and register the characteristic parameters of the TMJ, among which condylography instruments are validated for the accurate clinical registration of the condylar path. Sagittal condylar inclination (SCI) is one of the most important parameters, tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…The condylar inclination was evaluated when the condyle motion was 5 mm in the present study, as described by Slavicek[ 13 ]. Minimal differences were observed between the SCI and TCI values of individuals with Class I and Class II, consistent with the findings of previous studies[ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The condylar inclination was evaluated when the condyle motion was 5 mm in the present study, as described by Slavicek[ 13 ]. Minimal differences were observed between the SCI and TCI values of individuals with Class I and Class II, consistent with the findings of previous studies[ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Given that the device must be placed inside the mandible, this interferes with natural movement during mastication. An advantage of this system is the possibilty to record condylar movement [77].…”
Section: Discussionmentioning
confidence: 99%
“…Moga et al [ 7 ] explored the theme of root resorption as a side effect of orthodontic treatment using Finite Element Analysis (FEA) based on Tresca criteria. Dragus et al [ 8 ] assessed sagittal condylar inclination using an ultrasonic jaw tracking device, providing valuable information for both gnathologists and prosthodontists. Alwadei et al [ 9 ] identified risk factors for sleep-disordered breathing in 1866 children aged 6–12 years.…”
mentioning
confidence: 99%